THE IMPROVEMENT OF PHYSICAL FITNESS THROUGH THE CHEERFUL AND COLORFUL CIRCUIT GAME - Susanti, Rikza Azharona (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This research aims to find out how the process of increasing the physical fitness and the improvement of the physical fitness of grade B Kindergarten students through cheerful colours circuit game. The research was carried out in Gardini kindergarten in East Jakarta from January to March 2014. The research used action research method according to action research model of Kemmis and Mc. Taggart made through two cycles consisting of 7 sessions in the first cycle and 4 sessions in the second cycle. The cycle consists of four steps: a) planning, b) action (acting), c) observation (observing), and d) reflection (reflecting). The subjects were grade B in Gardini Kindergarten in East Jakarta consisting of 10 children. The data was collected by the research instrument which refers to the dimensions of physical fitness. The end result of this study showed an increase in physical fitness of children that is evidenced by the acquisition of classical physical fitness scores pre-action reaching 52.28%. After the first cycle had increased, the score reached 87.19% and the second cycle was obtained satisfactory classical scores reached 94.74%